APLIKASI WOOD PLACTIC COMPOSITE SEBAGAI PEREDAM KEBISINGAN AKTIVITAS JALAN KERETA API MODEL KRISTAL SONIK PERSEGI - Handayani, Dewi; Soeryodarundio, Koosdaryanti; Savira, Syafa Maajid (Universitas PGRI Semarang, 2025)
Noise is an unwanted sound from an activity over a period of time that can interfere with human health and environmental comfort. One of the noise caused by transportation activities is train noise. To reduce the noise, it can be achieved by building a noise dampening building between the railroad and the residential area. An attempt to create a sustainable noise reducer is Wood Platic Composite (WPC) which is made in the form of sonic crystals. This research aims to analyze the potential application of WPC with square sonic crystal model as a noise reducer for railway activities. This research uses an experimental method conducted in a residential area near the railroad tracks by testing the sound intensity of sonic crystals made from square lattice WPC with a diameter of 8.2 cm and a height of 2 meters. The test was conducted by placing the sonic crystal 3 meters away from the railroad axle, while the Sound Level Meter (SLM) was placed 1, 2, and 3 meters behind the sonic crystal. The method of data collection and analysis in this study used the Ministry of Environment No. 48 of 1996. The results showed that the sonic crystal made from square lattice WPC can reduce noise by 13.54%.